2021
DOI: 10.3389/fonc.2021.626499
|View full text |Cite
|
Sign up to set email alerts
|

Training and Validation of Deep Learning-Based Auto-Segmentation Models for Lung Stereotactic Ablative Radiotherapy Using Retrospective Radiotherapy Planning Contours

Abstract: PurposeDeep learning-based auto-segmented contour (DC) models require high quality data for their development, and previous studies have typically used prospectively produced contours, which can be resource intensive and time consuming to obtain. The aim of this study was to investigate the feasibility of using retrospective peer-reviewed radiotherapy planning contours in the training and evaluation of DC models for lung stereotactic ablative radiotherapy (SABR).MethodsUsing commercial deep learning-based auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Somewhat related, Wong et al described their RT patient selection and expert OAR segmentation efforts towards DL-based autosegmentation model evaluation, inclusive of capturing inter-expert variability (20). In a later report, the same institution described their expert OAR dataset preparation for model training and validation for a different anatomical site (21). The general sparsity of prior reporting may be indicative of a difficult peer review barrier (or perhaps a perception of a difficult peer review barrier)the potential challenges being that this and similar reports could be easily discarded as either non-hypothesis-driven or nonhypothesis-generating, or that they might be discounted under micro-dissection due to lack of novelty of constituent methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somewhat related, Wong et al described their RT patient selection and expert OAR segmentation efforts towards DL-based autosegmentation model evaluation, inclusive of capturing inter-expert variability (20). In a later report, the same institution described their expert OAR dataset preparation for model training and validation for a different anatomical site (21). The general sparsity of prior reporting may be indicative of a difficult peer review barrier (or perhaps a perception of a difficult peer review barrier)the potential challenges being that this and similar reports could be easily discarded as either non-hypothesis-driven or nonhypothesis-generating, or that they might be discounted under micro-dissection due to lack of novelty of constituent methods.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have benefited from a virtual explosion in the application of deep convolutional neural networks (hereafter referred to as deep learning, or DL) for tackling complex imaging-related problems. In the context of RT, arguably the best-realized example of DL has been organ-at-risk (OAR) CT and MRI segmentation used as a starting point for the RT planning process (1,4,6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Currently, numerous vendors provide commercial autosegmentation solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical implementation of AC systems is providing benchmark data for the comparison and validation of such systems. Various studies have tested the potential role of AC software in different districts, obtaining results that seem to suggest the possibility of developing such systems in clinical practice [ 17 , 18 , 19 , 22 , 23 , 25 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various experiences regarding clinical validation of AC models have already been reported in the literature, including testing AI-based delineation in different anatomical districts with single-institution workflow [ 17 ]. These trials tested AC models in multi-institutions validation groups, with the stated aim of demonstrating the validity of such systems in more complex RT treatment scenarios [ 18 , 19 ]. Furthermore, various studies have demonstrated that manual segmentation suffers from high inter-observers variability, and approaches to reduce such a source of uncertainty have been the subject of recent studies [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Registered CT images were used for delineating parotid and submandibular glands. Limbus AI [25] was used for preliminary auto-segmentation of the glands, which were then manually refined by a single senior radiation oncologist, Jonn Wu.…”
Section: Datasetmentioning
confidence: 99%